ANALISIS PENGARUH TINGKAT PENGETAHUAN, SIKAP, DAN MOTIVASI PERAWAT TERHADAP KEBERHASILAN PENERAPAN PATIENT SAFETY DIRSU TANGSEL - Mulanda, Monica Tri; Windiyaningsih, Cicilia; Kodyat, Alih Germas (LPPM Universitas Respati Indonesia, 2026)
Patient safety is carried out by all patient services in ensuring the quality of service. One strategy in designing a patient safety system is how to recognize errors so that they can be seen and immediate action can be taken to correct the effects that occur. Efforts to recognize and report these errors are made through the reporting system. The reporting rate in health services is still relatively low, as is the case in RSU Tangsel. The research aims to determine the influence of nurses' knowledge and motivation on nurses' attitudes in reporting patient safety incidents at RSU Tangsel. The research was conducted in June 2024 using a quantitative research design with a cross-sectional approach. Data collection was carried out using a questionnaire distributed to 100 nurses who worked at RSU Tangsel. Data were analyzed using PLS (Partial Least Square). The results of the research show that knowledge influences attitudes (t-statistic 3.613, direct effect coefficient 0.400), motivation influences attitudes (t-statistic 5.216, direct effect coefficient 0.473), knowledge influences motivation (t-statistic 3.289, direct effect coefficient 0.434), knowledge influencing attitudes through motivation (t-statistic 2.782, indirect effect coefficient 0.205) There is a positive and significant influence on knowledge on attitudes, knowledge on motivation, motivation on attitudes, and knowledge on attitudes through motivation. Knowledge is the most dominant influence on nurses' attitudes in reporting IKP at RSU Tangsel Keywords: Patient safety incident reports, knowledge of reporting patient safety incidents, attitudes towards reporting patient safety incidents, motivation to report patient safety incidents